Mechanistic exploration of the copper(i) phosphide synthesis in phosphonium-based and phosphorus-free ionic liquids. Issue 43 (20th October 2017) - Lê Anh, Mai; Wolff, Alexander; Kaiser, Martin; Yogendra, Sivathmeehan; Weigand, Jan J.; Pallmann, Julia; Brunner, Eike; Ruck, Michael; Doert, Thomas
Abstract : The transformation of red phosphorus into P4 and the surface activation of copper enable the quantitative formation of copper(i ) phosphide. Abstract : The mechanism of the synthesis of copper(i ) phosphide (Cu3− x P) in the ionic liquid (IL) trihexyl(tetradecyl)phosphonium chloride ([P66614 ][Cl]) was investigated. The phosphide formation is promoted by a transformation of red phosphorus (Pred ) into mobile P4 molecules and a surface activation of copper caused by the IL including the Brønsted acidic impurity. The surface activation is important to obtain a quantitative product yield. Moreover, we demonstrate that single-phase Cu3− x P can also be synthesized in the nitrogen-based IL tetrabutylammonium chloride ([N4444 ][Cl]). Further substitution of the anion of the IL using tetrabutylammonium bromide ([N4444 ][Br]) or the complete replacement of the IL by a deep eutectic solvent consisting of adipic acid and betaine do not lead to single-phase Cu3− x P. Therefore, the nature of the anions present in the IL also seems to be relevant for the convenient phosphidization reaction.